A variation of superficial palmar arch formed alone by ulnar artery: a case report - Karey, Geetha Devi Venkatanaga; Rayudu, Raja Madhava; Toleti, Sarada (International Journal of Research in Medical Sciences, 2017)
Superficial palmar arterial arch is an arterial arcade, which is a dominant vascular structure of the palm. It is defined as the anastomoses between the superficial branch of the ulnar artery and the superficial palmar branch of the radial artery. The superficial palmar arch completed by anastomosing with one of the branches of radial artery, i.e. with arteria radialis indicis, arteria princeps pollicis, arteria nervi mediana. The present study reporting a variation of superficial palmar arch which is formed alone by superficial branch of ulnar artery and it is also giving branches to radial side of index finger and to the thumb. Normally the branch to the radial side of index finger receives branch from superficial terminal branch of radial artery and it is known as arteria radiclis indicis. The ARI was given by ulnar artery from the terminal part of radial side along with the princeps pollicis branch. The knowledge of variations of the vascular arches warrants the surgeons while performing surgeries on hands, such as arterial repairs, vascular graft applications.